Mono- and multinuclear pincer-type Ru(II) complex catalysts and their catalytic applications - Liu, Tingting; Wang, Liandi; Wu, Kaikai; Wang, Qingfu; Yu, Zhengkun (Inorganica Chimica Acta, 2023)
[Display omitted] •Highly active mono- and multinuclear Ru(II) complex catalysts.•Applied in various borrowing hydrogen strategy reations.•Low catalyst loading for TH reaction (0.005-0.2 mol% Ru). Various pincer-type ruthenium(II) complexes were developed from our laboratories and herein the relevant advance is summarized from a viewpoint of their synthesis and organic synthetic applications as homogeneous catalysts. The investigated Ru(II)–NNN and Ru(II)–NNNN-type complexes exhibited highly catalytic activities in the transfer hydrogenation of ketones, C–C bond formation from alcohols and ketones, and dehydrogenation. RuH complexes were identified or considered as the catalytically active intermediates for these transformations. This review deals with the following subjects: (i) mononuclear ruthenium(II) pincer complexes with high catalytic activity in (asymmetric) transfer hydrogenation of ketones; (ii) multinuclear ruthenium(II) complexes for transfer hydrogenation of ketones; (iii) mononuclear ruthenium(II) complexes for other reactions such as Oppenauer-type oxidation, β-alkylation of secondary alcohols, synthesis of multisubstituted heterocycles, acceptorless dehydrogenation of N-heterocycles and secondary alcohols.